NGS analysis of collagen type I genes in Polish patients with Osteogenesis imperfecta: a nationwide multicenter study - Kinga Sałacińska; Iwona Pinkier; Lena Rutkowska; Danuta Chlebna-Sokół; Elżbieta Jakubowska-Pietkiewicz; Izabela Michałus; Łukasz Kępczyński; Dominik Salachna; Nina Wieczorek-Cichecka; Małgorzata Piotrowicz; Tatiana Chilarska; Aleksander Jamsheer; et al. (Frontiers in Endocrinology, 2023)
Osteogenesis imperfecta (OI) is a rare genetic disorder of the connective tissue. It presents with a wide spectrum of skeletal and extraskeletal features, and ranges in severity from mild to perinatal lethal. The disease is characterized by a heterogeneous genetic background, where approximately 85%–90% of cases have dominantly inherited heterozygous pathogenic variants located in the COL1A1 and COL1A2 genes. This paper presents the results of the first nationwide study, performed on a large cohort of 197 Polish OI patients. Variants were identified using a next-generation sequencing (NGS) custom gene panel and multiplex ligation probe amplification (MLPA) assay. The following OI types were observed: 1 (42%), 2 (3%), 3 (35%), and 4 (20%). Collagen type I pathogenic variants were reported in 108 families. Alterations were observed in α1 and α2 in 70% and 30% of cases, respectively. The presented paper reports 97 distinct causative variants and expands the OI database with 38 novel pathogenic changes. It also enabled the identification of the first glycine-to-tryptophan substitution in the COL1A1 gene and brought new insights into the clinical severity associated with variants localized in “lethal regions”. Our results contribute to a better understanding of the clinical and genetic aspects of OI.